Artificial Intelligence in Radiology Residency Training - Forney, Michael C.; McBride, Aaron F. (Seminars in Musculoskeletal Radiology, 2020)
Artificial intelligence (AI) is an emerging technology that brings a wide array of new tools to the field of radiology. AI will certainly have an impact on the day-to-day work of radiologists in the coming decades, thus training programs must prepare radiology residents adequately for their future careers. Radiology training programs should aim to give residents an understanding of the fundamentals and types of AI in radiology, the broad areas AI can be applied in radiology, how to assess AI applications in radiology, and resources available to build their knowledge in IA applications in radiology.
Keywords: artificial intelligence; residency; radiology; training